Sociolinguistic Awareness and ESP Curriculum Design: A Framework for Enhancing Authenticity and Learner Engagement - Eslam Yacoub (Universitas Kapuas, 2026)
This study investigates the integration of sociolinguistic awareness - encompassing culture, professional identity, power relations, and discipline-specific discourse norms - into English for Specific Purposes (ESP) curriculum design, and its implications for task authenticity and learner engagement. A qualitative-dominant mixed-methods design triangulated systematic document analysis of 64 curriculum units, semi-structured interviews with 15 ESP faculty members, and a questionnaire administered to 338 students across computer science, engineering, pharmacy, and business programs. Document analysis revealed a hierarchical pattern: professional discourse norms were most explicitly addressed, while power relations were absent in nearly two-thirds of materials. Interview data identified systemic constraints - curricular rigidity, misaligned assessment, and insufficient pedagogical training - that inhibit implementation. Student data demonstrated that sociolinguistically framed tasks were perceived as significantly more authentic and were associated with higher cognitive, behavioral, and emotional engagement. These findings collectively indicate that the marginalization of sociolinguistic dimensions represents a structural limitation on ESP curriculum effectiveness. The study proposes an evidence-based framework that repositions sociolinguistic awareness as a core design principle, essential for preparing learners for meaningful participation in professional discourse communities.